Uwarunkowania i pożądane kierunki ekonomizacji działań w gospodarce finansowej miasta (na przykładzie miasta Łodzi) - Wartalska, Magdalena (Conditions and Desired Directions for the Economization of Actions in the Financial Economy of a City (Based on the Example of the City of Łódź), 2005)
The aim of this article is to specify main problems and directions of improvement in the management of the city's finances. The article is based on the assumption that supply and quality of a given public service as well as increasing competition of the city in the process of conquering different advantages such as gaining new investors, financial benefits and localization of private sector institutions depend on decisions and actions of the city. Management of finances should be directed towards the development of widely understood enterprise, which leads to the creation of harmonious city's functional structure in which there is a balance between exogenic functions of the city - the ones of the surroundings and endogenic functions - servicing local community. This is the fundamental for pointing the appropriate direction for the allocation of public resources. Although economic aims usually are defeated by the community oriented aims in the economy of the city (and criteria of efficiency stay in opposition to the criteria which are compulsory in the sphere of public service) the insufficient financial resources in comparison with realised public tasks impose on local authorities the duty to conduct deep analysis (including the costs of conducting these tasks and the structure of budget expenses) for the purpose of pointing out and further realisation of the most significant projects essential for spatial, communal, and economical development of the commune.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 303-313